(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Atopic isolated cheilitis is mainly combined with the most significant changes in immunocompetent cells and, first of all, characterizing the T-cell link. In atopic forms of cheilitis, all classes of immunoglobulins are involved in detoxification mechanisms, as evidenced by positive correlations with endogenous intoxication indicators. In addition, tension in the elimination function of the kidneys and salivary glands is noted.